Use of Reversed-Phase hplc for the Determination of Free Formaldehyde Content in Nail Polishes - Maldonado Santoyo, María; Hernández Guerrero, Erika; Morales López, Gladys; Arcibar Orozco, Javier Antonio; Lambert, Juliette Alexandra; Bañuelos Díaz, Jennifer Alexis (Ingeniería Solidaria, 2017)
Introduction: This article derives from the research titled Use of reversed-phase hplc for the determination of free formaldehyde content in nail polishes, conducted in 2015 at the Center for Applied Innovation in Competitive Technologies (ciatec). Method: The free formaldehyde content was determined in 50 samples of nail polishes of various brands marketed in León, Guanajuato, Mexico. Samples were treated according to the iso 17226-1:2003 method, with slight modifications: 2 ± 0.1 g of nail polishes were weighed in 100 ml Erlenmeyer flasks, 40 ml of 0.1 % sodium dodecyl sulfonate were added; the samples were then capped and left in a water bath at 40 °C under constant stirring for 60 minutes; they were subsequently filtered, and aliquots of each sample were taken for derivatization with 0.3 % 2,4-dinitrophenylhydrazine for 60 minutes. The analytical determination was achieved by reversed-phase hplc-diode array detection. Results: All nail polish samples tested were below the regulatory limit of 0.2 % free formaldehyde content in cosmetics. Conclusions: We obtained toxicologically relevant information on free formaldehyde in nail polishes, in addition to checking the versatility and robustness of the test method.